Keterkaitan Antara Transparansi Dengan Sifat Tablig Dalam Penerapan Prinsip GCG - Illabillah, Valiyan Rahmad; Zakaria, Yahya Wahyu Zacky; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Corporate Governance are known principles to protect business trust. The problem of developing good corporate governance practices coincided with the occurrence of financial cases involving several large companies such as Enron and WorldCom. Indonesia, where the majority of the population is Muslim, must understand the principles of good corporate governance according to sharia in running its business. The purpose of making this research is to introduce how to apply good and correct GCG principles to ensure the sustainability of company operations with the characteristics of Islamic Corporate Governance so that the company's operations are carried out according to the objectives of this research. This research refers to research from various sources, using descriptive analysis.